2014
DOI: 10.1186/1756-0500-7-427
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquinol reduces gamma glutamyltransferase as a marker of oxidative stress in humans

Abstract: BackgroundThe reduced form of Coenzyme Q10 (CoQ10), ubiquinol (Q10H2), serves as a potent antioxidant in mitochondria and lipid membranes. There is evidence that Q10H2 protects against oxidative events in lipids, proteins and DNA. Serum gamma-glutamyltransferase (GGT) activity is associated with cardiovascular diseases. In a physiological range, activity of GGT is a potential early and sensitive marker of inflammation and oxidative stress.In this study, we first examined the relationship between CoQ10 status a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 38 publications
0
24
2
1
Order By: Relevance
“…A possible explanation for this result might be a consequence of the increased GSH levels (ffi39%), since GGT promotes the turnover of GSH levels (Halliwell & Gutteridge, 2007). The vitamin E levels remained fairly constant in t 0 compared to controls, thus suggesting that the increased levels of GSH and UA are indeed playing their important role as ROS scavengers, since UA is responsible for approximately 60% of plasma ROS elimination, therefore preserving vitamin E plasma levels (Drozdz et al, 1998;Onur et al, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…A possible explanation for this result might be a consequence of the increased GSH levels (ffi39%), since GGT promotes the turnover of GSH levels (Halliwell & Gutteridge, 2007). The vitamin E levels remained fairly constant in t 0 compared to controls, thus suggesting that the increased levels of GSH and UA are indeed playing their important role as ROS scavengers, since UA is responsible for approximately 60% of plasma ROS elimination, therefore preserving vitamin E plasma levels (Drozdz et al, 1998;Onur et al, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…In our study, although serum leptin levels in the CoQ10-treated group were marginally reduced, this difference was not statistically significant compared to the control group, and it may be due to the low dose of CoQ10 and the short period of the study. Asker showed that coadministration of CoQ10 for 8 weeks in mice with monosodium glutamate modulated leptin gene expression [14] due to its role as a modulator of gene expression and inflammatory processes [34]. However, our literature review did not find any human studies in regard to this issue.…”
Section: Discussionmentioning
confidence: 92%
“…In a similar study, Yuvaraj et al showed that coadministration of CoQ10 and B vitamins (riboflavin and niacin) for 90 days reduced the serum activity levels of liver-related enzymes (i.e., GGT and AST) in Tamoxifen-treated women with breast cancer [35]. In another study, Onur et al [34] reported that 2 weeks' supplementation with 150 mg/day of CoQ10 in healthy subjects significantly reduced serum GGT activity as well as GGT1 gene expression. In their cross-sectional study, they found that GGT levels were strongly and positively associated with CoQ10 status.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One possible reason might be the oxidative stress suppressing effects of DC. Because liver enzyme AST is related to oxidative stress and elevated all-cause mortality [39] . In this regard, Abrokwah et al showed that oral gavage of aqueous cocoa suspension (1 ml/day) for 48 days had no effects on AST, ALT and Alkp in rat [40] .…”
Section: Acknowledgmentmentioning
confidence: 99%